Drivers of Support for the Populist Radical Left and Populist Radical Right in Belgium : An Analysis of the VB and the PVDA-PTB Vote at the 2019 Elections - Goovaerts, Ine; Kern, Anna; van Haute, Emilie; Marien, Sofie (Politics of the Low Countries, 2020)
This study investigates how protest attitudes and ideological considerations affected the 2019 election results in Belgium, and particularly the vote for the radical right-wing populist party Vlaams Belang (VB) and for the radical left-wing populist party Partij van de Arbeid-Parti du Travail de Belgique (PVDA-PTB). Our results confirm that both protest attitudes and ideological considerations play a role to distinguish radical populist voters from mainstream party voters in general. However, when opposed to their second-best choice, we show that particularly protest attitudes matter. Moreover, in comparing radical right- and left-wing populist voters, the article disentangles the respective weight of these drivers on the two ends of the political spectrum. Being able to portray itself as an alternative to mainstream can give these parties an edge among a certain category of voters, albeit this position is also difficult to hold in the long run.